2016
DOI: 10.3389/fphar.2016.00352
|View full text |Cite
|
Sign up to set email alerts
|

Methanolic Extract of Morinda citrifolia L. (Noni) Unripe Fruit Attenuates Ethanol-Induced Conditioned Place Preferences in Mice

Abstract: Phytotherapy is an emerging field successfully utilized to treat various chronic diseases including alcohol dependence. In the present study, we examined the effect of the standardized methanolic extract of Morinda citrifolia Linn. unripe fruit (MMC), on compulsive ethanol-seeking behavior using the mouse conditioned place preference (CPP) test. CPP was established by injections of ethanol (2 g/kg, i.p.) in a 12-day conditioning schedule in mice. The effect of MMC and the reference drug, acamprosate (ACAM), on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Hence, moxidectin may reduce alcohol-linked CPP via the NMDA receptor. These results are similar to those published in several studies, which found ethanol-induced CPP with NMDA receptor antagonists on average (Biała and Kotlińska 1999;Aguilar et al 2009;Khan and Pandy 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Hence, moxidectin may reduce alcohol-linked CPP via the NMDA receptor. These results are similar to those published in several studies, which found ethanol-induced CPP with NMDA receptor antagonists on average (Biała and Kotlińska 1999;Aguilar et al 2009;Khan and Pandy 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Most of them evaluated rats or mice behavior in conditioned place preference tests, induced by the administration of drugs such as alcohol and heroin. In both cases, it was demonstrated that the administration of the methanolic extract of M. citrifolia fruits decreased the effects of heroin and alcohol dependence (Khan and Pandy, ; Narasingam et al , , Pandy and Khan, ).…”
Section: Neuroprotective Activitymentioning
confidence: 99%
“…and ACAM (300mg/kg,p.o.) had no considerable influence on the reinstatement caused by ethanol priming injection.Our new findings show that MMC has an antidopaminergic activity in both invivo and evivo investigations.Therefore we postulate that MMC influences the expression and facilitation of extinction of ethanol induced CPPSare due to its antidopaminergic activity.Due to presence of scopoletin and rutin as phytochemical constituents in noni, responsible for many pharmacological activities and antidopaminergic activity.The forgoing study concludes that MMC attenuated expression and accelerated the extinction of ethanol induced CPP in mice 3 .…”
Section: Anticraving Activity Against Alcohol Dependence Invivo Studiesmentioning
confidence: 88%
“…One of the most single powerful sources of CNS disorders is depression 2 .Conventional drugs such as antidepressants, antianxiety, antipsychotics shows minimal effect and have adverse effects such as extra pyramidal effects. In modern medicine, phytotherapy research is an integral part for the discovery and discovery of novel drugs 3 .…”
Section: Introductionmentioning
confidence: 99%